Innovation theory and occupational mobility: The case of fish traders at Mtera Dam-Tanzania - Kimeme Joseph; Itika Josephat (Entrepreneurship and Business Development Research Cluster, 2026)
The main objective of this study was to identify factors that explain occupational mobility among fish traders. Previous studies have focused on formal employment and have been done mainly in developed countries. Lack of similar knowledge in African settings means that interventions meant to introduce new occupations or to perpetuate existing ones may not be scientifically managed.